Side Effects of 5‐Alpha Reductase Inhibitors: A Comprehensive Review. Issue 1 (30th April 2013) - Trost, Landon; Saitz, Theodore R.; Hellstrom, Wayne J.G.
Abstract: Introduction: 5α‐reductase inhibitors (5ARI) include finasteride and dutasteride, and are commonly prescribed in the treatment of benign prostatic hyperplasia and androgenic alopecia. 5ARIs are associated with several known adverse effects (AEs), with varying reported prevalence rates. Aim: The aim was to review and summarize findings from published literature detailing AEs associated with 5ARI use. A secondary aim was to review potential mechanisms of action, which may account for these observed and reported AEs. Methods: A PubMed search was conducted on articles published from 1992 to 2012, which reported AEs with 5ARIs. Priority was given to randomized, placebo‐controlled trials. Studies investigating potential mechanisms of action for 5ARIs were included for review. Main Outcome Measures: AE data reported from available trials were summarized and reviewed. Results: Reported AEs with 5ARIs include sexual dysfunction, infertility, mood disorders, gynecomastia, high‐grade prostate cancer, breast cancer, and cardiovascular morbidity/risk factors, although their true association, prevalence, causality, and clinical significance remain unclear. A pooled summary of all randomized, placebo‐controlled trials evaluating 5ARIs (N = 62, 827) revealed slightly increased rates over placebo for decreased libido (1.5%), erectile dysfunction (ED) (1.6%), ejaculatory dysfunction (EjD) (3.4%), and gynecomastia (1.3%). The limited data available on the impact of 5ARIs on mood disorders demonstrate statistically significant (although clinically minimal) differences in rates of depression and/or anxiety. Similarly, there are limited reports of reversible, diminished fertility among susceptible individuals. Post‐marketing surveillance reports have questioned the actual prevalence of AEs associated with 5ARI use and suggest the possibility of persistent symptoms after drug discontinuation. Well‐designed studies evaluating these reports are needed. Conclusions: 5ARIs are associated with slightly increased rates of decreased libido, ED, EjD, gynecomastia, depression, and/or anxiety. Further studies directed at identifying prevalence rates and persistence of symptoms beyond drug discontinuation are required to assess causality.Trost L, Saitz TR, and Hellstrom WJG. Side effects of 5‐alpha reductase inhibitors: A comprehensive review. Sex Med Rev 2013;1:24–41.